Foot problem and foot care practices among diabetic patients in a primary care clinic, Kuala Lumpur - Jamani, Nurjasmine Aida; Muhammad, Noor Azimah; Jaafar, Aida; Ahmad, Saharuddin; Tohit, Noorlaili (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2018)
Foot problems are very common in diabetic patients but may go unnoticed by the patients and undiagnosed by the healthcare providers leading to substantial morbidity and amputations. The aims of this study were to assess patient’s foot care practices, awareness on their foot condition as well as to determine the prevalence of diabetic foot problem and its associated factors. Methods: This was a cross sectional study conducted among diabetic patients in a primary care clinic in Kuala Lumpur. Patients with diabetes, aged more than 18 years were selected using systematic random sampling technique. Patients were requested to answer a set of self-administered pre-tested questionnaire that obtain information on their socio-demographic profiles, diabetic clinical data, awareness on their feet condition and foot care practice. A trained clinician examined patients’ feet using a standard foot examination protocol. Results: A total of 166 patients with diabetes participated in this study. Nearly half of the patients (70, 42.2%) had diabetic foot problem but only 31 (18.7%) of them were aware of their foot condition. The three common problem were trophic changes of the skin (92.8%), followed with hair loss (71.1%) and callosity (65.7%). The independent associated factors for foot problem were increasing age (AOR=1.05, 95% CI 1.015-1.095; p<0.05) and lower education level (AOR=2.32, 95% CI 1.092-4.908; p< .05). Many of the participants did not practice a proper foot care such as not using a proper foot wear, not inspecting their feet daily and thoroughly dry their feet. Conclusion: There was a high prevalent of diabetic foot problem in these patients especially among elderly and those with a lower education level but not many of them were aware of their problem. They were found to have poor foot care practice. Therefore, efforts need to be targeted on increasing patients’ awareness on their foot condition and improve their understanding on foot care practice. In addition, it is important for health professionals to carry out regular foot examination as many of the diabetic patients may not aware of their problem.